Targeted gadolinium-loaded dendrimer nanoparticles for tumor-specific magnetic resonance contrast enhancement - Scott D Swanson (Dove Medical Press, 2008)
Scott D Swanson1, Jolanta F Kukowska-Latallo2, Anil K Patri5, Chunyan Chen6, Song Ge4, Zhengyi Cao3, Alina Kotlyar3, Andrea T East7, James R Baker31Department of Radiology, The University of Michigan Medical School, 2Department of Internal Medicine, The University of Michigan Medical School, 3Michigan Nanotechnology Institute for Medicine and Biological Sciences, The University of Michigan, 4Applied Physics, The University of Michigan, MD, USA; 5Present address: National Cancer Institute at Frederick (Contractor), MD, USA; 6Present address: Intel Corporation, Chandler, AZ, USA; 7Present address: Stritch School of Medicine, Chicago, ILL, USAAbstract: A target-specific MRI contrast agent for tumor cells expressing high affinity folate receptor was synthesized using generation five (G5) of polyamidoamine (PAMAM) dendrimer. Surface modified dendrimer was functionalized for targeting with folic acid (FA) and the remaining terminal primary amines of the dendrimer were conjugated with the bifunctional NCS-DOTA chelator that forms stable complexes with gadolinium (Gd III). Dendrimer-DOTA conjugates were then complexed with GdCl3, followed by ICP-OES as well as MRI measurement of their longitudinal relaxivity (T1 s−1 mM−1) of water. In xenograft tumors established in immunodeficient (SCID) mice with KB human epithelial cancer cells expressing folate receptor (FAR), the 3D MRI results showed specific and statistically significant signal enhancement in tumors generated with targeted Gd(III)-DOTA-G5-FA compared with signal generated by non-targeted Gd(III)-DOTA-G5 contrast nanoparticle. The targeted dendrimer contrast nanoparticles infiltrated tumor and were retained in tumor cells up to 48 hours post-injection of targeted contrast nanoparticle. The presence of folic acid on the dendrimer resulted in specific delivery of the nanoparticle to tissues and xenograft tumor cells expressing folate receptor in vivo. We present the specificity of the dendrimer nanoparticles for targeted cancer imaging with the prolonged clearance time compared with the current clinically approved gadodiamide (OmniscanTM) contrast agent. Potential application of this approach may include determination of the folate receptor status of tumors and monitoring of drug therapy.Keywords: dendrimer, DOTA, gadolinium, MRI, folate receptor